Strategic Leadership: A Systematic Literature Review and Hybrid Bibliometric Analysis - Muhammad Deny; Cristoporus Esandra Murta Kurniawan; Irfan Handoko; Rusfian Effendi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study presents a comprehensive review of strategic leadership, employing a systematic literature review (SLR) and bibliometric analysis to evaluate its evolution and significance in contemporary organizational practices. By examining 733 articles on strategic leadership from the Scopus database, this research highlights key trends, gaps, and future directions in the field. The findings reveal that strategic leadership is increasingly relevant across various sectors, particularly with the rise of digital transformation and the growing influence of artificial intelligence. Additionally, the study underscores the importance of integrating leadership theories with practical applications to enhance organizational performance. The bibliometric analysis further identifies prominent authors, institutions, and countries contributing to strategic leadership research, suggesting areas where future inquiries could focus, including the intersection of leadership and innovation. The results provide valuable insights for both academics and practitioners, advancing the understanding of strategic leadership's impact on organizational success.